A Review of Coffee Kombucha Brewing and Health Effects as a Fermented Beverage - Sasongko, Devi Purnamasari (Poltekkes Kemenkes Surakarta, 2025)
Background: Coffee kombucha, or what many kombucha brewers call koffucha, is one of the new varieties of kombucha, by replacing the tea infusion with coffee extract. However, the method of making koffucha still varies, like the coffee varieties, coffee extraction method, SCOBY and starter ratio, sugar ratio, fermentation time, and second fermentation. This review aims to examine koffucha brewing methods and its potential health benefits. Methods: This study reviewed the study about koffucha from previous literature using PRISMA method. The literature was gathered through a systematic search of PubMed, Scopus, and Google Scholar databases. Search terms included